- URGENSI REGULASI PENCEMARAN LINTAS BATAS NEGARA DARI AKTIVITAS RIG DI LEPAS PANTAI (STUDI KASUS MONTARA) : - - Alissa Nur Zahrani; Anto Ismu Budianto (Reformasi Hukum Trisakti, 2023)
Transboundary pollution is an environmental dispute that requires serious attention. International law does not specifically regulate state responsibility for transboundary pollution from rig activities. The problems raised by the author in this research are, what regulations can be made to fill the legal vacuum regarding transboundary pollution caused by rig activities and what compensation is provided by PTT Exploration and Production (PTTEP) Australasia for marine pollution due to oil spills in Timor Sea. This research uses a Normative Law research method that is analytical description, sourced from primary, secondary and tertiary data which is analyzed qualitatively so that the conclusions are deductive. Based on the research results, regulations that can be made to overcome cross-border pollution due to offshore rig activities can be in the form of international conventions and bilateral agreements between Indonesia and Australia. The compensation provided by Australia is not sufficient to cover the losses borne by the Indonesian people, thus Australia only fulfills its responsibilities based on the principle of Responsibility